O cotidiano escolar como base para pensar o papel político da escola - Brito, Diogo Mendes de (2020)
This work is in the field of reflection on the political role of education, being linked to the line of research: State, Politics and History of Education of the Graduate Program in Education at the Federal University of Goiás. It refers to a research carried out in/of the School daily life experienced by the 3rd year high school students and teachers at public school in the state of Goiás. In this scenario, we objective to understand how school routine, as an analytical category, is a fundamental factor to think about fulfilling the role policy of school education. This political role of education is based on the contributions of the thinker Hannah Arendt, in view of the fact that everyday theorists, whose lens made it possible for us to look at the everyday researched in a theoretical way, that is, “not everyday” were founded from the works of the thinkers Agnes Heller and Henri Lefebvre. Our investigation focused on the multiple “seemingly insignificant” activities of daily life, in order to categorize such actions in an attempt to perceive in these activities the possibility of a reflection on the political role of the school as institution. In addition to interviews, analysis of normative documents from the state education network and notes in a field diary, it was necessary to adopt an unconventional academic methodology: that of “immersing” in the daily lives of students and teachers, so that the researcher became integral part of the researched object. The research carried out allowed us to realize that the school routine unbalances and hinders the good relationship that should exist between what Agnes Heller called the individuality and genericity of individuals, where the first one seems to be prevalecing in the process of training students, that is, in the new students that are being inserted into an old world.